U.S. Mutual Funds: Measuring Performance and Persistence in Performance - Zhang, Jingjing (2010)
This paper investigates the performance of U.S. mutual funds using a survivorship-free sample of 2083 mutual funds from 2005 to 2010. My results suggest strong evidence that actively managed mutual funds underperform the benchmark, indicated by statistically insignificant alphas. Among three types of equity fund with different investment objectives, there are no apparent differences in risk-adjusted abnormal return. Using Treynor&Mazuy model I find little evidence for market timing abilities from U.S. mutual funds. Further, in the short term, there is no evidence for persistence in superior performance but strong evidence for persistence in the underperformance.